Aktivitas Antioksidan Ekstrak, Fraksi dan Golongan SenyawaKimia Daun Premna oblongata Miq - Katrin, Katrin; Bendra, Atika (UI Scholars Hub, 2015)
Indonesia has many kinds of plants which can be used as natural antioxidant sources. This study was focused on antioxidant activity of Cincau Perdu leaves extract (Premna oblongata Miq.) using 1-Diphenyl-2-picrylhydrazyl (DPPH) methods. P. oblongata leaves was extracted using n-hexane, ethylacetate and methanol. It was found that methanol extract has the highest activity with IC50 value 20.01 μg/mL. The extract with highest antioxidant activity were fractionated with accelerated column chromatography and were earned 6 combination fractions. The antioxidant activity of each combination fractions were tested by DPPH methods. Fraction-5 showed the highest activity as antioxidant with IC50 23.51 μg/mL. The compounds of the active fractions were flavonoid, glikon, saponin and tannin.